2015
DOI: 10.7717/peerj.1141
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing captures varying temporal patterns of vegetation between human-altered and natural landscapes

Abstract: Global change has led to shifts in phenology, potentially disrupting species interactions such as plant–pollinator relationships. Advances in remote sensing techniques allow one to detect vegetation phenological diversity between different land use types, but it is not clear how this translates to other communities in the ecosystem. Here, we investigated the phenological diversity of the vegetation across a human-altered landscape including urban, agricultural, and natural land use types. We found that the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 43 publications
(54 reference statements)
0
34
0
1
Order By: Relevance
“…Resource availability across landscapes, however, is often seasonally variable (Kremen ). Examining NDVI (normalized difference vegetation index), Leong and Roderick () found that urban, agricultural, and natural areas provided pulses of floral resources at different times of year. Further, pollinator abundance tracked these changes in resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Resource availability across landscapes, however, is often seasonally variable (Kremen ). Examining NDVI (normalized difference vegetation index), Leong and Roderick () found that urban, agricultural, and natural areas provided pulses of floral resources at different times of year. Further, pollinator abundance tracked these changes in resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Because town areas have less green space and are mostly ornamental plants, anthropogenic supplements of water and nutrients could prolong the vegetation growing season. It causes the growth of vegetation to be relatively stable [65]. Meanwhile, several studies demonstrated that anthropogenic disturbances can assist in the selection of more productive ecosystems [32].…”
Section: Disturbance Of Anthropogenic Factors On Vegetation Greening mentioning
confidence: 99%
“…2. Remote sensing data such NDVI often reflect human-altered vegetation patterns and ought not be used as covariates in PNV mapping (Leong and Roderick, 2015).…”
Section: /35mentioning
confidence: 99%